ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE PADA INSERT BUDAYA "TANAMPO" DI SRIWIJAYA RADIO - Muhammad Alif Abel Athallah; M Mifta Farid (Jurnal Prodi Ilmu Komunikasi, 2023)
Mass communication is communication that aimed to the general public that contains information or messages. To support this communication, various kinds of mass media were formed. One of mass communication media is radio. Based on its function, radio is a place to get various kinds of information that has a different way of delivery from other mass media. Radio can also be a means of entertainment where you can listen to music of any genre. Radio is one of the media that has the greatest power as a medium of imagination so that it plays the theatre of mind. This research aims to analyze the semiotics that exist in the cultural insert "Tanampo" in Sriwjaya Radio based on Ferdinand de Saussures theory, there are aspects of the signifier and the signified. In this research, an analysis of the sign in each scene is presented based on Ferdinand de Saussure theory. The researcher uses a qualitative descriptive method to describe the situation to be observed more specifically and in depth with data sources obtained from primary and secondary data and using the reception analysis approach and focus group discussion methods. Based on the results of the analysis that has been carried out as a whole in each scene, aspects of the insert are developed so that researchers can conclude that the message conveyed through the cultural insert "Tanampo" on Sriwijaya Radio can be well received by listeners.